SOPHISTICATED EPISTEMIC BELIEFS: AN INTERPRETATIVE PHENOMOLOGICAL ANALYSIS OF STUDENTS' TASK-BASED LEARNING EXPERIENCES - Ive Emaliana; Ni'matul Lailiyah (Erudio Journal of Educational Innovation, 2018)
This article describes a phenomological study in which the researchers explored students' experiences in joining task-based learning (TBL) activities. Semi-structured in-depth interviews were conducted with six participants from low, medium, and high achievement levels who had completed one semester of introduction to research method course. Using interpretative phenomenological analysis (IPA), the researchers identified four primary themes representing the lived experience and meaning found in the participants' experience of task-based learning activities: (1) constructive communication; (2) helping others; (3) learning strategies; (4) sense of responsibility. The findings both support and contribute new aspects to the knowledge of this experience. The results also point to sophisticated epistemic beliefs level own by the students as the essence of the phenomenon of task-based learning activities.